Paraguay : Staff Report for the 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
The Paraguayan economy suffered setbacks throughout 2011-12 owing to drought, export ban, and inflation. Recovery measures have been under way with active government intervention in the implementation of a new budget, tax reforms, and new monetary and fiscal policies. The central bank has undertaken measures to increase non-agricultural revenue and strengthen the cooperative sector. Although it commended fiscal prudence, the Executive Board advised on an improved tax regime, promotion of public investment, and the need to devise long-term strategies.